SLANG AS A METALANGUAGE VARIABLE IN THE HISTORICAL AND COMPARATIVE ASPECTS - Borys, D. (Linguistic and Conceptual Worldviews, 2019)
The article examines the term slang in the light of its polysemantic nature in English, Ukrainian, Polish, Hungarian, French, Italian, and Spanish language studies. Approaches to defining slang in English are specified and systematized. Interlingual semantic equivalents utilized to name English slang counterparts in the other six analyzed national language terminological systems are established.